Novel relations : the transformation of kinship in English literature and culture, 1748-1818 - Perry, Ruth, 1943- (Cambridge University Press, 2004)
Ruth Perry describes the eighteenth-century transformation of the English family as a function of major social changes. She uses social history, literary analysis and anthropological kinship theory to examine texts by Austen, Richardson, Burney, and many others. This important study will be of interest to social and literary historians.